Boron – A potential goiterogen?. (July 2017) - Popova, Elizaveta V.; Tinkov, Alexey A.; Ajsuvakova, Olga P.; Skalnaya, Margarita G.; Skalny, Anatoly V.
Abstract: The iodine deficiency disorders (IDD) include a variety of disturbances such as decreased fertility, increased perinatal and infant mortality, impaired physical and intellectual development, mental retardation, cretinism, hypothyroidism, and endemic goiter (EG). The occurrence of the latter is determined by interplay between genetic and environmental factors. The major environmental factor is iodine status that is required for normal thyroid hormone synthesis. However, other factors like intake of micronutrients and goiterogens also have a significant impact. Essential and toxic trace elements both play a significant role in thyroid physiology. We hypothesize that in terms of overexposure boron may serve as a potential goiterogen. In particular, it is proposed that boron overload may impair thyroid physiology ultimately leading to goiter formation. Certain studies provide evidential support of the hypothesis. In particular, it has been demonstrated that serum and urinary B levels are characterized by a negative association with thyroid hormone levels in exposed subjects. Single indications on the potential efficiency of B in hypothyroidism also exist. Moreover, the levels of B were found to be interrelated with thyroid volume in children environmentally exposed to boron. Experimental studies also demonstrated a significant impact of boron on thyroid structure and hormone levels. Finally, the high rate of B cumulation in thyroid may also indicate that thyroid is the target for B activity. Chemical properties of iodine and boron also provide a background for certain competition. However, it is questionable whether these interactions may occur in the biological systems. Further clinical and experimental studies are required to support the hypothesis of the involvement of boron overexposure in goiter formation. If such association will be confirmed and the potential mechanisms elucidated, it will help to regulate the incidence of hypothyroidism and goiter in endemic regions with high boron levels in soil and water.